Career competencies experience: a study among Malaysian vocational and technical students - Mohd Ariffim, Ruhaida; Bakar, Ab. Rahim; Hamzah, Ramlah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This study was conducted with the aim of determining a relationship between career competencies based on academic achievement among community college students. This study was also carried out for the purpose of determining career competency differences based on gender, choice of field of study and interest in field of study. Findings from previous researches clearly showed that career competencies is capable of influencing the preparedness of students to enter the world of work because changes in the dynamic work environment undeniably demands that they are always equipped with elements of career development. Data collection was conducted employing a survey method. Questionnaires were distributed to 356 final year students in selected community colleges based on stratified random sampling. The findings showed that the career competencies of students was at a high level (mean = 3.94, standard deviation = 0.45). The results of t-tests showed that there was no difference in career competencies based on gender (t=1.294, p > 0.05). Subsequently, results of t-tests showed that there were differences between career competencies based on choice of field of study (t =-2.172, p < 0.05). Besides this, the findings also indicated that there was a significant difference for career competencies based on interest in field of study. The findings also clearly showed that there is no relationship between career competencies and students’ academic achievement in community college (r = -0.007, p =0.894). An individual needs to take the initiative to develop a career network and have the desire to keep learning to enhance career competencies.